2019
DOI: 10.1016/j.calphad.2019.101678
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of Al2MgC2 and thermodynamic modeling of the Al–C–Mg system - Application to grain refinement of Mg–Al alloys

Abstract: In the scope of supporting the development of Mg-Al alloys and related materials, an experimental study coupled with a CALPHAD thermodynamic modeling of the Al-C-Mg system was conducted. The peritectic decomposition of Al2MgC2 to form Al4C3, graphite and a liquid phase was measured at 1559±10 K by DTA. In order to model the Mg solubility in Al4C3, DFT calculations were performed on the end-member phases Mg4C3, Al2Mg2C3 and Mg2Al2C3 and it was shown that Mg substitutes on the Al2 crystallographic site of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…1 in the Supplementary Information, where it can be seen that only the trigonal T2-Al2MgC2 structure is consistent with the experimental Kikuchi patterns from this phase. Furthermore, we note that T2-Al2MgC2 is the expected equilibrium phase in AZ91 containing impurity carbon from recent work on the thermodynamics of the Al-C-Mg system [13,40].…”
Section: T2-al2mgc2 Pre-existing In the Az91 Ingotmentioning
confidence: 61%
See 2 more Smart Citations
“…1 in the Supplementary Information, where it can be seen that only the trigonal T2-Al2MgC2 structure is consistent with the experimental Kikuchi patterns from this phase. Furthermore, we note that T2-Al2MgC2 is the expected equilibrium phase in AZ91 containing impurity carbon from recent work on the thermodynamics of the Al-C-Mg system [13,40].…”
Section: T2-al2mgc2 Pre-existing In the Az91 Ingotmentioning
confidence: 61%
“…Emley [12] suggested that, during superheating, the walls of steel crucibles are decarburised resulting in carbon pickup to the Mg alloy, and that more carbon pickup occurs from new crucibles since they contain more carbon in the surface layers. When the carbon content exceeds the solubility limit of an AZ91 melt, carbides form and according to recent thermodynamic calculations the expected carbide in Mg-9Al-0.5C (wt.%) is Al2MgC2 [13].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For carbon-reinforced MMCs, the Al 2 MgC 2 phase is formed along the grain boundary with the increase in Al content. Deffrennes et al [25] obtained a 70Mg-19Al-11Cwt% sample in a Ta crucible and quenched at 1273 K for 240 h to obtain Al 2 MgC 2 crystal. A relatively accurate ternary system model was obtained by comparing the decomposition temperatures calculated by differential thermal analysis (DTA) and discrete Fourier transform (DFT).…”
Section: Mg-al-zn (Az) Matrix Compositesmentioning
confidence: 99%
“…Figure 1. The 91Mg-9Al wt% alloy was heated to 1000 k and modified by 0.5wt% C. The phase (a) linear and (b) logarithmic mass fraction images of the Scheil solidification model were obtained[25]. SEM morphologies of (c) Mg6Zn and (d) ZnO-0.5GO/Mg6Zn[27].…”
mentioning
confidence: 99%